Reflecting on 60 years of Academic Korea Expertise in Australia: (Missed) Opportunities and Challenges Ahead - Elfving-Hwang, Joanna (Korea Research Centre of WA, 2022)
Korean Studies in Australia is typically seen as pure language and cultural training rather than a critical area of research and academic discipline.